2014
DOI: 10.20344/amp.5090
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Inflammatory Bowel Disease: Is your Patient at Risk of Non-Adherence?

Abstract: Acta Med Port 2014 Sep-Oct;27(5):576-580 RESUMOIntrodução: A adesão à terapêutica é um aspecto chave para a eficácia da terapêutica. O objectivo deste estudo foi avaliar a frequên-cia e factores de risco associados à não adesão à terapêutica na doença inflamatória intestinal. ABSTRACT Introduction:Adherence to therapy is a key factor when analyzing the efficacy of a treatment in clinical practice. The aim of our study was to assess the frequency of non-adherence to treatment among patients with inflammatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
8
0
4
Order By: Relevance
“…In previously published studies parameters associated with greater adherence to medical therapy in IBD patients were age, follow-up by a gastroenterologist, and immunosuppressant use [8,9]. Lower rates of treatment adherence were associated with employment status, high scores on the Obstacles to Medication Use Scale, short disease duration, high education level, dissatisfaction with the patient-doctor relationship, mood disorders, and age younger than 40 [7][8][9][10]49]. Moreover, patients' personal beliefs about the IBD and its treatment are important, potentially modifiable, determinants of both adherence and nonadherence [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously published studies parameters associated with greater adherence to medical therapy in IBD patients were age, follow-up by a gastroenterologist, and immunosuppressant use [8,9]. Lower rates of treatment adherence were associated with employment status, high scores on the Obstacles to Medication Use Scale, short disease duration, high education level, dissatisfaction with the patient-doctor relationship, mood disorders, and age younger than 40 [7][8][9][10]49]. Moreover, patients' personal beliefs about the IBD and its treatment are important, potentially modifiable, determinants of both adherence and nonadherence [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that non-adherence to prescribed long-term treatment is a major determinant of treatment efficacy in inflammatory bowel disease (IBD) patients and represents a common problem in IBD management in clinical practice. The frequency of non-adherence ranges from 18 to 30% as reported in several recent international trials [7][8][9][10]. In a recent study of potential triggers for IBD flares, which included non-steroidal anti-inflammatory drug use, antibiotic use, stressful life events, cigarette smoking, infections, travel in the preceding 3 months, and medication adherence, only the last one resulted to be significantly associated with flares [11].…”
Section: Introductionmentioning
confidence: 99%
“…Com a exceção do estudo de Margalho e colaboradores, 27 todos os estudos têm âmbito regional ou local: sete na região Norte, 26,[32][33]36,[41][42]49 sete na região de Lisboa e Vale do Tejo, 28,30,34,40,[43][44]48 quatro na região Centro, 25,35,45,51 dois no Alentejo 31,37 e dois no Algarve. 29,50 Em dois dos estudos não é clara a região do País onde os mesmos decorreram; [38][39] também o estudo de Reis 24 decorreu simultaneamente num hospital de Lisboa e num hospital do Porto.…”
Section: Local Do Estudo/recolha Dos Dadosunclassified
“…Dos estudos selecionados, em 15 a amostra foi obtida a partir de utentes seguidos em consultas hospitalares de especialidade; [24][25][26][27]29,[32][33][34][35][38][39][42][43]48,51 em seis estudos, 28,31,[36][37]41,49 a partir de utentes seguidos nos cuidados de saúde primários -desde uma Unidade de Saúde Familiar no estudo de Chin e colaboradores 28 até à Administração Regional de Saúde do Alentejo, no estudo de Moita; 31 dois estudos recorreram a utentes de farmácias comunitárias; 30,45 em dois estudos, a amostra foi constituída por utilizadores de centros de dia 44,50 e, no último, por utentes seguidos na Associação Protetora dos Diabéticos de Portugal. 40…”
Section: Local Do Estudo/recolha Dos Dadosunclassified
See 1 more Smart Citation